Ontogenetic changes in cranial vault thickness in a modern sample of Homo sapiens - Anzelmo, Marisol (2014)
Objectives This work assesses cranial vault thickness (CVT) ontogenetic changes using a computed tomography database to register thickness across multiple regions. Methods Vault images of 143 individuals from 0 to 31 years old were analyzed by thickness semiautomatic measurements. For each individual, we obtained a thickness mean measure (TMM) and its coefficient of variation, a measure of endocranial volume (EV), the distribution of relative frequencies of thickness—relative frequency polygon, and a topographic mapping that shows the thickness arrangement through a chromatic scale. Ontogenetic changes of these variables were evaluated by different regression models (TMM vs. age, EV vs. age, TMM vs. EV) and visual comparisons between the age groups. Results TMM increased during ontogeny until the onset of adulthood without sex differences, but the most accelerated growth rates occur during the first 6 years of postnatal life. TMM variations were associated with EV only in infants and children, but not in later periods. The polygons showed a flattening during ontogeny, probably due to an increase in thickness variation within individuals. However, the adult pattern of thickness arrangement, with the lateral region thinner than the regions near sagittal plane, was detected from infancy. Conclusion The pattern of thickness arrangement is established early in ontogeny but CVT increases and changes in distribution until adolescence. Several factors may influence CVT, such as the brain, muscles, vessels, and sutures.